Supervising the difficult employee - McGill, Ann M; Swanson, Mandi (Chicago : Jack Wilson and Associations, 1994)
This video offers detailed guidance on recognizing and addressing problems such as chronic absenteeism, abrasive behavior and policy violations
Editor, Greg St Clair
Keywords: Supervision of employees